"Nor ever lightning char thy grain"1: establishing archaeologically relevant charring conditions and their effect on glume wheat grain morphology. Issue 1 (11th September 2015) - Charles, M.; Forster, E.; Wallace, M.; Jones, G.
Abstract : Charring is the most ubiquitous form of preservation of plant material on archaeological sites, occurring wherever people use heat. The usefulness of preserved seeds for a range of analytical techniques is dependent on the conditions under which they were heated. In this study, we investigate the effect of experimental heating on two types of glume wheat grain (einkorn and emmer) under a range of conditions, with the intention of establishing the likely parameters for the generation of virtually undamaged, undistorted charred cereal grain on archaeological sites. The results show that grain morphology is very sensitive to the charring conditions, especially temperature, and that well preserved grains with little distortion are produced at relatively low temperatures (220–240°C). The implications of these findings for the study of grain morphology, biomolecules and chemical composition are assessed. Data availability The authors confirm that all data underlying the findings are fully available without restriction. All relevant data are contained within the paper.